JUVENILE JUSTICE LEGISLATION RELATING TO CHILDREN IN NEED OF CARE AND PROTECTION: INDIAN SCENARIO (International Journal of Food and Nutritional Sciences, 2022)
India has undergone significant legal reforms to address the unique challenges faced by vulnerable children, emphasizing rehabilitation and protection over punitive measures. The legislative framework primarily revolves around the Juvenile Justice (Care and Protection of Children) Act, with subsequent amendments reflecting the evolving understanding of juvenile rights.The Juvenile Justice Act recognizes the special status of children in need of care and protection, encompassing those without adequate family support, victims of abuse, and abandoned or orphaned children. The legislation aims to provide a comprehensive support system, ensuring their welfare, rehabilitation, and reintegration into society. Key provisions include the establishment of Juvenile Justice Boards, Child Welfare Committees, and Special Juvenile Police Units to handle cases involving children in conflict with the law or those in need of care and protection.The Indian legal framework emphasizes a child-centric approach, promoting the best interests of the child as a primary consideration in all decisions. It introduces non-institutional alternatives such as foster care, adoption, and sponsorship, aiming to create a nurturing environment for children deprived of a stable family life. Additionally, the Act incorporates provisions for counseling, education, and skill development, acknowledging the importance of holistic development for these children.